Direito à desconexão do trabalho como instrumento de proteção à saúde do trabalhador - Braga, Eduardo Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In contemporary society, taken over by advanced technique, the right to disconnect, the right to non-work, are important instruments for the preservation of workers' occupational health. The changes in the types of services provisions in the workplace or elsewhere, due to the opportunities offered by modern techniques, tend to render the worker constantly connected to his work in detriment of his private life. The dangerous confusion between personal and professional life can cause physical and mental illnesses. The fundamental right of workers not to work during their moments of rest, relaxation, and family time has, in this context, utmost importance and must be respected by all, including the government and the private sector. Since modern technique acts as a kind of facilitator when it comes to the increasing exploitation of human beings in the workplace, it is also through it that we must seek ways to prevent the ever increasing exploitation of workers. The technique which allows constant work at all times, should also act as a way to prevent it. Changes in attitude, particularly when it comes to the employer, given the technical innovations, are absolutely necessary to safeguard a person's right to disconnect herself from work. The effective respect of the workers' non-specific right to disconnect from their job depends on the actions of all parts involved, spontaneously or not. Only through the effective disconnection from work is that we are able to speak of a worker's full personality development in his path to become a social and cultural being.

Na sociedade contemporânea, tomada pela técnica avançada, o direito à desconexão, direito ao não-trabalho, é um importante instrumento para a preservação da saúde do trabalho do trabalhador. Alterações havidas nas formas de prestação de serviços, seja no ambiente de trabalho ou fora dele, em decorrência das facilidades proporcionadas pela técnica moderna tendem a deixar o trabalhador constantemente conectado com o seu labor, em detrimento de sua vida particular. O perigoso amálgama entre vida particular e profissional é capaz de causar adoecimento físico e mental. O direito fundamental do trabalhador de não trabalhar em seus momentos de descanso, lazer e convívio familiar passar a ter, nesse contexto, importância ímpar, devendo ser por todos respeitados, poder público ou particulares. Como a técnica moderna atua como uma espécie de facilitador do aumento da exploração do ser humano que trabalha, é através dela que se deve buscar modos de impedir a instrumentalização crescente do trabalhador. A técnica que permite o trabalho constante, a todo tempo, também deve servir para impedi-lo. Mudanças de postura, sobretudo do empregador, diante das inovações técnicas, são absolutamente necessárias à salvaguarda do direito de desconexão do homem de seu trabalho. O respeito efetivo ao direito inespecífico do trabalhador de se desconectar de seu trabalho depende da atuação de todos os envolvidos, espontaneamente ou não. Somente com a efetiva desconexão do trabalho que se pode falar em pleno desenvolvimento da personalidade do trabalhador, em sua construção com ser social e cultural.
Keywords: Direito do trabalho; Trabalho - Aspectos sociais; Trabalhadores - Proteção; Saúde do trabalhador - Aspectos jurídicos